PAX3 haploinsufficiency in Maine Coon cats with dominant blue eyes and hearing loss resembling the human Waardenburg syndrome - Rudd Garces, Gabriela; Farke, Daniela; Schmidt, Martin J; Letko, Anna; Schirl, Katja; Abitbol, Marie; Leeb, Tosso; Lyons, Leslie A; Lühken, Gesine; Justus Liebig University Giessen (My University, 2024)
This study investigated the dominant blue eyes (DBE) trait linked to hearing impairment and variable white spotting in Maine Coon cats. Fifty-eight animals descending from 2 different DBE lineages, the Dutch and the Topaz lines, were sampled. They comprised 48 cats from the Dutch bloodline, including 9 green-eyed and 31 blue-eyed cats, with some individuals exhibiting signs of deafness, and 8 stillborn kittens. Samples from the Topaz lineage included 10 blue-eyed animals. A brainstem auditory evoked response test revealed a reduced to absent response to auditory stimuli and absent physiological waveforms in all of the 8 examined DBE animals. We sequenced the genome of 2 affected cats from the Dutch line and searched for variants in 19 candidate genes for the human Waardenburg syndrome and pigmentary disorders. This search yielded 9 private protein-changing candidate variants in the genes PAX3, EDN3, KIT, OCA2, SLC24A5, HERC2, and TYRP1. The genotype–phenotype cosegregation was observed for the PAX3 variant within all animals from the Dutch lineage. The mutant allele was absent from 461 control genomes and 241 additionally genotyped green-eyed Maine Coons. We considered the PAX3 variant as the most plausible candidate—a heterozygous nonsense single base pair substitution in exon 6 of PAX3 (NC_051841.1:g.205,787,310G>A, XM_019838731.3:c.937C>T, XP_019694290.1:p.Gln313*), predicted to result in a premature stop codon. PAX3 variants cause auditory–pigmentary syndrome in humans, horses, and mice. Together with the comparative data from other species, our findings strongly suggest PAX3:c.937C>T (OMIA:001688-9685) as the most likely candidate variant for the DBE, deafness, and minimal white spotting in the Maine Coon Dutch line. Finally, we propose the designation of DBERE (Rociri Elvis Dominant Blue Eyes) allele in the domestic cat.
Keywords: ddc:630